A systematic review exploring the factors that contribute to increased primary care physician turnover in socio-economically deprived areas. - Jasmine Lee; Evangelos Kontopantelis (PLoS ONE)
Background The declining trend in the number of primary care physicians worldwide has led to shortages especially within socioeconomically deprived areas. Socioeconomically deprived areas in the context of this review are defined by regions where there are lower levels of income and access to essential services such as primary healthcare compared to other areas. This shortage contributes to a higher incidence of preventable hospital admissions, unnecessarily straining healthcare infrastructure and negatively affecting patient outcomes. Previous studies have often been limited in scope, focusing on isolated factors or specific regions. Therefore, the objective of this systematic review is to synthesise current research to provide a better understanding of the underlying causes of this high turnover, ultimately informing strategies to address the global shortage of primary care physicians. Methods This systematic review followed the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Refer to S1 Table for the PRISMA 2020 checklist. A comprehensive search was conducted across PubMed (1970 to September 2024) and Embase (1974 to September 2024). The eligibility criteria included quantitative empirical studies that included a measurement of at least one of the factors behind increased primary care physician turnover or retention within socio-economically deprived or disadvantaged areas. However, the included studies were required to employ a specific methodology for classifying or defining socioeconomic deprivation. The references were screened, the studies selected, the data extracted, and the risk of bias assessed using the ROBINS-I tool, with both reviewers in agreement. Results Thirteen studies were identified. The factors measured in the studies driving increased turnover in deprived areas included region of work (n = 7), income (n = 2), burnout (n = 2) and social values (n = 2). Some studies found additional challenges specific to socioeconomically deprived areas, such as familial concerns about regional safety, limited employment opportunities for spouses, or personal career development challenges. However, some studies identified increased hours and sickness presenteeism as stronger contributors to burnout. However, this link can be presumed to be stronger in deprived areas due to staffing shortages, though none of the studies in this systematic review have directly measured this correlation. Though longer-term methods of retention within socioeconomically deprived areas included more collaborative working environments and flexible working hours, this can also be applied to benefit healthcare settings across all regions. Conclusions The studies reviewed have consistently highlighted the repeating cycle of persistent staff shortages contributing to an increased turnover rate within disadvantaged areas internationally. Therefore, implementation of targeted policies by governments and healthcare organisations is required to retain primary care physicians within these areas to ultimately improve and standardise patient care.